Literary Images of Self and Other in Irish and Ukrainian Famine Fiction - Krol, Tatiana (Literature and Cultural Studies E-Books Online, Collection 2026, 2025)
This book is a comparative imagological study of novelistic representations of the Irish and Ukrainian Great Famines. It examines the formation of stereotypical perceptions between nations in Irish and Ukrainian fiction. Focusing on the novels The Silent People (1962) by Walter Macken, The Hungry Land (1986) by Michael Mullen, Maria: A Chronicle of a Life (1934) by Ulas Samchuk and Sweet Snow (2013) by Alexander J. Motyl, the author compares and contrasts images of the Self and the Other created in Irish and Ukrainian novels about famine and investigates ways in which stereotypical perceptions between nations are forged and disseminated. The author argues that negative attitudes between people and/or nations largely depend on power relations.